Crossover cinema : cross-cultural film from production to reception - Khorana, Sukhmani, 1984- (New York : Routledge, 2013)
'Cinematic products in the twenty-first century increasingly emerge from, engage with, and are consumed in cross-cultural settings. While there have been a number of terms used to describe cinematic forms that do not bear allegiance to a single nation in terms of conceptualization, content, finance and/or viewership, this volume contends that'crossover cinema' is the most apt contemporary description for those aspects of contemporary cinema on which it focuses. This contention is provoked by an appreciation of the cross-cultural reality of our post-globalization twenty-first century world. This volume both outlines the history of usage of the term and grounds it theoretically in ways that emphasize the personal/poetic in addition to the political. Each of the three sections of the volume then considers crossover film from one of three perspectives: production, the texts themselves, and distribution and consumption.'--
Includes bibliographical references and index.
Keywords: Motion picture industry -- Economic aspects -- Foreign countries